Position Control for Automatic Assembly Equipment Using a New Hybrid Fuzzy Controller - Zhang, Longjie; Kang, Mingxia; Liu, Xinhua; Li, Zhixiong (Elektronika ir Elektrotechnika, 2024)
Automatic assembly equipment is the key to improving the efficiency and quality of workpiece assembly. The precision of assembly directly influences the overall quality of the assembled product. To optimise the position control accuracy in the automatic assembly equipment, a variable universe fuzzy proportional integral (VUFPI) controller optimised by the sparrow search algorithm (SSA) is developed in this paper. The developed controller adopts the SSA to adjust in real time the universe of the fuzzy controller according to the deviation of the servo system. The servo system model is established to evaluate the performance of the proposed SSA-VUFPI controller; furthermore, the SSA-VUFPI controller is implemented in the automatic assembly equipment for experimental evaluation. The analysis results demonstrate that the proposed SSA-VUFPI controller is capable of improving the anti-interference ability and position accuracy of the servo system compared to traditional PI, VUFPI, and currently used back propagation neural network proportional-integral-derivative (BP-PID), fractional-order PID (FOPID), and SSA-PID controllers. Moreover, it effectively improves the position accuracy of the workpiece and ultimately improves the quality of the assembly.